A practical approach to serials cataloging - Smith, Lynn S. (Greenwich, Connecticut : Jai Press, 1978)
The stages in the development of the national union catalogue and software used for database design and development with different computer systems are discussed. The integration of the database with an e-mail service for routeing of library/user request information is also described. Findings - It was found that NUCSSI is an ideal access tool and is indispensable in supporting document supply. Regular updating of the database is enhanced with the online access granted to the participating libraries via the internet.
Includes index.
Includes bibliographical references: p. 397-413.
aia 29/6/17
Loans
Keywords: Cataloging of serial publications